Idealist philosophy of space : Kant's criticism of Berkeley - Storrie, Stefan (Trinity College (Dublin, Ireland). Philosophy Department, 2009)
In this thesis I have argued that Kant and Berkeley both took our experience of things in space to be real and veridical. Further, and what I take to be the most striking conclusion from this thesis, is that in fact these two ‘idealists’ took the human body to play a constitutive role as a necessary condition for outer experience and our geometrical knowledge.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin